The Relationships between Knowledge, The Number of Drugs Used and Drug Use Problems among Elderly Patients with Chronic Illness at A Medical Clinic - Meetathip, Sukrita (Journal of The Royal Thai Army Nurses, 2023)
This research aimed to study drug use knowledge, number, and problems related to drug use among elderly patients. The sample group was 88 elderly patients with chronic diseases who received services at medical clinics. The research instruments consist of the questionnaires of knowledge of drug use and problems related to drug use with a content validity index of 0.92 and 0.92, respectively. The reliability was analyzed using the Kuder-Richardson formula (KR-20) of 0.79 and Cronbach’s alpha coefficient formula of 0.80, respectively. Data were analyzed by descriptive statistics; frequency, percentage, mean, and standard deviation. The relationships among variables were analyzed using Pearson’s correlation coefficient and Spearman’s rank correlation coefficient statistic. The results showed that the research samples had a score of drug use knowledge at a good level (M = 10.73, SD = 1.53) and a problem related to drug use at a low level (M = 1.36, SD = .65). Drug use knowledge was negatively associated with drug problems statistically (r = .194, P<.05). Besides, the number of drugs used was a statistically significant positive correlation with drug use problems (r = .185, P<.05). The results of the study can be used for nurses to educate elderly patients with chronic diseases who receive a variety of medications to promote rational drug use.